(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
Homicide is not receding with the passage of time. They continue to constitute the most important and significant of the heinous crimes by homosepians. The rate of homicide has been the major indicator of violence levels all around the world1. Here, we made a study on homicides at mortuary of Civil Hospital, Ahmedabad during the one year period of 2005 with special reference to demographic variables like month, day and time of homicide, age and sex of the victims, duration of survival after receiving fatal injury, cause of death, type of weapon, number of assailants, motive for homicide and the relation of accused with the victim.